Histological and immunohistochemical analysis of meat-based food preparations - Migaldi, Mario; Rossi, Giulio; Sgambato, Alessandro; Farinetti, Alberto; Mattioli, Anna Vittoria (Progress in Nutrition, 2016)
This study aimed to verify the possibility to use standard morphologically-based techniques to assess the tissue composition of typical meat-based food preparations. Twenty-six different types of meat-based products were randomly selected and histologically analyzed. A variety of tissues were identified including connective tissue, blood vessels, peripheral nerve, adipose tissue, glandular tissue, skin, bone and cartilage and plant material. Glial fibrillary acidic protein staining was also used to evaluate the presence of brain tissue. The results obtained suggest that most of the analyzed products display a more complex composition than the one suggested by package label. These findings confirms the suitability of standard morphological techniques to examine the histology of meat-based food preparations and suggest their use for the control and quality certification of these types of products.